The effect of computer assisted instruction on students' achievement in the teaching of the subject of activity [Elementlerde Aktiflik Kavraminin öǧretilmesinde Bilgisayar Destekli öǧretim Materyali Kullanilmasinin ögrenci Basarisi üzerine Etkisi] - (:unkn) unknown (My University, 2012)
[No abstract available]
Keywords: Activity; Chemistry education; Computer assisted instruction